2020
DOI: 10.1055/s-0040-1701983
|View full text |Cite
|
Sign up to set email alerts
|

From Patient Engagement to Precision Oncology: Leveraging Informatics to Advance Cancer Care

Abstract: Objectives: Conduct a survey of the literature for advancements in cancer informatics over the last three years in three specific areas where there has been unprecedented growth: 1) digital health; 2) machine learning; and 3) precision oncology. We also highlight the ethical implications and future opportunities within each area. Methods: A search was conducted over a three-year period in two electronic databases (PubMed, Google Scholar) to identify peer-reviewed articles and conference proceedings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…In the context of the evolving landscape of cancer care in Japan, the National Cancer Center Hospital’s Survivorship Program plays a crucial role in shaping a compassionate and patient-centered approach to post-treatment care. Its commitment to addressing both medical and emotional needs marks it as a vital resource for individuals navigating life after cancer [ 30 ].…”
Section: Towards Shaping the Future Of Cancer Survivorship: Current G...mentioning
confidence: 99%
“…In the context of the evolving landscape of cancer care in Japan, the National Cancer Center Hospital’s Survivorship Program plays a crucial role in shaping a compassionate and patient-centered approach to post-treatment care. Its commitment to addressing both medical and emotional needs marks it as a vital resource for individuals navigating life after cancer [ 30 ].…”
Section: Towards Shaping the Future Of Cancer Survivorship: Current G...mentioning
confidence: 99%
“…Machine Learning (ML) has shown promise to revolutionize the healthcare industry (Topol, 2019;Griffin et al, 2020). From image classification and understanding to natural language processing, ML approaches have had many advancements and, in some cases, surpassed human performance (Esteva et al, 2017;Haenssle et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, humans go beyond the subcellular level and more attention should be given to the psychological dimensions related to health diseases ( Fioretti et al, 2016 ). Studies showed that psychological factors may impact cancer progression and development and collateral effects occurrence ( Spiegel and Kato, 1996 ; Butow et al, 2000 ; Turner-Cobb et al, 2001 ; Segerstrom, 2003 ), as well as patient engagement and commitment to treatment ( Kondylakis et al, 2019 ; Griffin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%